AVALIAÇÃO DOS EFEITOS DE DIFERENTES TIPOS DE CAL EM MISTURAS DE CONCRETO ASFÁLTICO - Budny, Jaelson; Hartman, Diego A.; Bock, André L.; Boeira, Fernando; Tizott, Rafael; Specht, Luciano P. (Salão do Conhecimento, 2013)
Resumo